Kajian Penggunaan Aset Zombie Ditinjau Prinsip Konservatisme Pada PT. Hadji Kalla - Nurjanna, Nurjanna; Anggraeni, Dewi (Patria Artha Journal of Accounting dan Financial Reporting, 2020)
This study aims to determine the study of the use of Zombie Assets in terms of the conservatism principle at PT. Hadji Kalla. This study uses a qualitative approach with descriptive analysis. The type of data used is secondary data and primary data. This study uses data collection techniques in the form of interviews, literature study and internet searching. The results of the study stated that the PT. Hadji Kalla, fixed assets that have expired or have book value of zero are not detailed in the financial statements, but only in total. Zombie Asset at PT. Hadji Kalla is 9,134 units or 71%. PT. Hadji Kalla uses the cost method, and that indicates that Zombie's assets in the company adhere to the principle of conservatism, but if you look at the measurement of accrual measures in 2017, 2018 and 2019, there is a difference in analysis, namely in 2017 the difference in negative accruals indicates that it adheres to the principle of conservatism. occurs because the costs incurred are quite large and too fast. In contrast to 2018 and 2019 showing a positive accrual difference, this happened because of the management policy in the finance accounting section to implement concept matching and this explained that in the last two years the assets of PT. Hadji Kalla does not adhere to the principle of conservatism.